Penerapan Strategi Promosi Pada Media Digital / Online Di Pt Gpi Logistics - Alden Nelson; Vinolia Angellius (STIE AMKOP, 2023)
Abstract In the city of Batam there are many Logistics Services which make Batam's growth high. Therefore, there are many Competitors and competitors which make it difficult for many companies to achieve company results. So that we will make promotional brochures that can help partners. The main problem that has been faced is the company's achievement targets that were not achieved. And to overcome this problem the author uses the Promotion method by distributing promotional brochures on Instagram social media. The results obtained after implementing the promotional methods that have been designed are the company's target and turnover achieved. The next recommendation is to always update social media regularly and always make visits to other companies. Keywords : Promotion, Logistics,Export, Import